2023
DOI: 10.2147/jir.s418106
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, Lymphocyte-to-Monocyte Ratio and Systemic Inflammation Response Index with Short-Term Functional Outcome in Patients with Acute Ischemic Stroke

Ya Xin Zhang,
Zhi Yuan Shen,
Yi Cun Jia
et al.

Abstract: Background and Purpose The aim of this study was to explore the relationship between functional prognosis and the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR) and systemic inflammatory response index (SIRI) in patients with acute ischemic stroke (AIS) at discharge. Methods A total of 861 patients with AIS were enrolled between January 2019 and December 2021. Blood cell counts were collected on admission. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, recent studies have shown that SIRI was associated with clinical outcomes in patients with stroke. 33,34 Furthermore, previous study showed that SIRI was an independent risk factor for mortality in patients with acute myocardial infarction. 35 In the present study, we found that patients with POD had higher NLR and SIRI before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown that SIRI was associated with clinical outcomes in patients with stroke. 33,34 Furthermore, previous study showed that SIRI was an independent risk factor for mortality in patients with acute myocardial infarction. 35 In the present study, we found that patients with POD had higher NLR and SIRI before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers including the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-inflammation index (SII), have been identified as emerging biomarkers that reflect the balance between innate immunity and adaptive immunity ( 11 ). These markers are used in prognosticating various conditions, such as cancer ( 12 , 13 ), cardiovascular diseases ( 14 ), acute ischemic strokes ( 15 , 16 ), and infectious diseases ( 17 ). The elevated NLR has been recognized as a noteworthy independent predictor for Parkinson’s disease (PD) ( 18 ), Alzheimer’s disease (AD) ( 19 , 20 ), and progressive supranuclear palsy (PSP) ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory markers including the neutrophil-to-lymphocyte ratio (NLR), platelet-tolymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and systemic immune-inflammation index (SII), have been identified as emerging biomarkers that reflect the balance between innate immunity and adaptive immunity (11). These markers are used in prognosticating various conditions, such as cancer (12,13), cardiovascular diseases (14), acute ischemic strokes (15,16), and infectious diseases (17). The elevated NLR has been recognized as a noteworthy independent predictor for Parkinson's disease (PD) (18), Alzheimer's disease (AD) (19,20), and progressive supranuclear palsy (PSP) (21).…”
Section: Introductionmentioning
confidence: 99%